Amyloid‐Related Imaging Abnormalities in the DIAN‐TU‐001 Trial of Gantenerumab and Solanezumab: Lessons from a Trial in Dominantly Inherited Alzheimer Disease. Issue 5 (13th October 2022) - Joseph‐Mathurin, Nelly; Llibre‐Guerra, Jorge J.; Li, Yan; McCullough, Austin A.; Hofmann, Carsten; Wojtowicz, Jakub; Park, Ethan; Wang, Guoqiao; Preboske, Gregory M.; Wang, Qing; Gordon, Brian A.; Chen, Charles D.; et al.
Abstract : Objective: To determine the characteristics of participants with amyloid‐related imaging abnormalities (ARIA) in a trial of gantenerumab or solanezumab in dominantly inherited Alzheimer disease (DIAD). Methods: 142 DIAD mutation carriers received either gantenerumab SC (n = 52), solanezumab IV (n = 50), or placebo (n = 40). Participants underwent assessments with the Clinical Dementia Rating® (CDR®), neuropsychological testing, CSF biomarkers, β‐amyloid positron emission tomography (PET), and magnetic resonance imaging (MRI) to monitor ARIA. Cross‐sectional and longitudinal analyses evaluated potential ARIA‐related risk factors. Results: Eleven participants developed ARIA‐E, including 3 with mild symptoms. No ARIA‐E was reported under solanezumab while gantenerumab was associated with ARIA‐E compared to placebo (odds ratio [OR] = 9.1, confidence interval [CI][1.2, 412.3]; p  = 0.021). Under gantenerumab, APOE‐ɛ4 carriers were more likely to develop ARIA‐E (OR = 5.0, CI[1.0, 30.4]; p  = 0.055), as were individuals with microhemorrhage at baseline (OR = 13.7, CI[1.2, 163.2]; p  = 0.039). No ARIA‐E was observed at the initial 225 mg/month gantenerumab dose, and most cases were observed at doses >675 mg. At first ARIA‐E occurrence, all ARIA‐E participants were amyloid‐PET+, 60% were CDR >0, 60% were past their estimated year to symptom onset, and 60% had also incident ARIA‐H. Most ARIA‐E radiologically resolved after dose adjustment and developing ARIA‐E did not significantly increase odds of trial discontinuation. ARIA‐E was more frequently observed in the occipital lobe (90%). ARIA‐E severity was associated with age at time of ARIA‐E. Interpretation: In DIAD, solanezumab was not associated with ARIA. Gantenerumab dose over 225 mg increased ARIA‐E risk, with additional risk for individuals APOE‐ɛ4(+) or with microhemorrhage. ARIA‐E was reversible on MRI in most cases, generally asymptomatic, without additional risk for trial discontinuation. ANN NEUROL 2022;92:729–744